PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA (Studi Putusan Nomor 28/Pid.susu/2015/PN.Krg. - JOHAN SAHBUDIN (2020)
Law enforcement against narcotics abuse in Indonesia still has problems. Abusers who are supposed to be victims but are used as perpetrators as regulated in Act Number 35 of 2009 concerning Narcotics. imprisonment for victims of class I narcotics abusers in Karang Anyar District Court decision number 28 / pid.sus / 2015 / PN.Krg. The criminal decision handed down was not in accordance with the objectives of Law Number 35 Year 2009 Regarding Narcotics. The imposition of criminal sanctions in 10 (ten) months of imprisonment has not yet brought about optimal coordination and cooperation in the resolution of Narcotics problems. The purpose of this study was to determine the practice of law enforcement against narcotics abuse offenders and to determine the basis for judges' considerations in dropping convictions of narcotics abuse offenses. The study was conducted using Normative Juridical research. The approach used is the legislative approach and case approach. Based on the results of the study, it was found that law enforcement for narcotics offenders prioritizes penal efforts. Narcotics abuse offenders should undergo rehabilitation prior to attempting a criminal offense. Keywords: narcotics abusers, narcotics, law enforcement